What Is the Best Discipline to Predict Overall Triathlon Performance? An Analysis of Sprint, Olympic, Ironman® 70.3, and Ironman® 140.6 - Sousa, Caio Victor; Aguiar, Samuel; Olher, Rafael Reis; Cunha, Rafael; Nikolaidis, Pantelis Theodoros; Villiger, Elias; Rosemann, Thomas; Knechtle, Beat (Frontiers in Physiology, 2021)
Objective: To analyze the proportion of dedication in each triathlon discipline (swimming, cycling and running) and the importance of each separate discipline to predict overall performance of elite triathletes across different triathlon distances. Methods: Data from 2015 to 2020 (n = 16,667) from official races and athletes in Sprint, Olympic Distance, IM 70.3 (Half Ironman distance) and IM 140.6 (Full Ironman distance) competitions were included. The proportion of each discipline was calculated individually and compared using general linear models by event distance, sex, and performance level. Automatic linear regression models were applied for each distance considering overall performance as the dependent variable. Results: A within-distance analysis showed that the best predictor for Sprint is cycling, for Olympic it is swimming, for IM 70.3 is cycling and for IM 140.6 is running. A between-distance analysis revealed that swimming is a better predictor in Olympic distance than in other triathlon distances. Cycling is a poor predictor for overall performance in IM 140.6, and the importance of running to predict overall performance is the highest in IM 140.6 and diminishes with decreasing race distance. Conclusion: Each discipline represents a different relative portion and importance to predict overall performance depending on the triathlon distance. Swimming is the most important predictor discipline in Sprint and Olympic Distance triathlon, cycling for Ironman 70.3 and running in Ironman 140.6.